2004
DOI: 10.1001/archinte.164.4.370
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fiber and Risk of Coronary Heart Disease

Abstract: Background: Few epidemiologic studies of dietary fiber intake and risk of coronary heart disease have compared fiber types (cereal, fruit, and vegetable) or included sex-specific results. The purpose of this study was to conduct a pooled analysis of dietary fiber and its subtypes and risk of coronary heart disease. Methods:We analyzed the original data from 10 prospective cohort studies from the United States and Europe to estimate the association between dietary fiber intake and the risk of coronary heart dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
344
4
11

Year Published

2005
2005
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 551 publications
(379 citation statements)
references
References 40 publications
20
344
4
11
Order By: Relevance
“…The absence of an association between FFQ-measured fibre and CHD risk among men was somewhat unexpected, given the inverse associations detected in previous cohort studies (Pietinen et al, 1996;Rimm et al, 1996;Todd et al, 1999;Wolk et al, 1999). Furthermore, in a pooled analysis, 11 out of the 16 cohort studies used FFQs, and the inverse effect size was similar for men and women (Pereira et al, 2004). However, within the pooled analysis, only a single study reported a significant, inverse association using an FFQ after adjustment for multiple covariates .…”
Section: Discussionmentioning
confidence: 78%
“…The absence of an association between FFQ-measured fibre and CHD risk among men was somewhat unexpected, given the inverse associations detected in previous cohort studies (Pietinen et al, 1996;Rimm et al, 1996;Todd et al, 1999;Wolk et al, 1999). Furthermore, in a pooled analysis, 11 out of the 16 cohort studies used FFQs, and the inverse effect size was similar for men and women (Pereira et al, 2004). However, within the pooled analysis, only a single study reported a significant, inverse association using an FFQ after adjustment for multiple covariates .…”
Section: Discussionmentioning
confidence: 78%
“…Thus, by way of mediating pathways (insulin resistance, lipids and systemic inflammation), low DF intake might be associated with a higher cardiovascular risk. A pooled analysis of prospective cohort studies found that a higher DF intake was inversely associated with the risk of coronary heart disease (Pereira et al, 2004). Other cohort studies have also reported lower incident coronary heart disease among participants with higher DF intakes (Todd et al, 1999;Bazzano et al, 2003).…”
Section: Introductionmentioning
confidence: 98%
“…The grain fiber as a single component has also been associated with significant risk reduction. For example, pooled analyses of 10 cohort studies reported a 10% reduced risk of cardiovascular disease with every 10 g/day increment in intake of cereal fiber (6).…”
Section: Introductionmentioning
confidence: 99%